Vietnam : 2007 Article IV Consultation-Staff Report; Staff Supplement and Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Vietnam has recorded continued strong economic performance since the conclusion of the last Article IV Consultation. GDP growth rose to 8.2 percent in 2006, with non-oil exports remaining an important engine of growth. Private investment has also expanded briskly. The near-term outlook remains broadly favorable, and Vietnam has good prospects for sustained growth and poverty reduction over the medium term, provided that the government can take timely action to rein in demand pressures.